2013
DOI: 10.1111/jeea.12006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Social Norms Using Coordination Games: Why Does Dictator Game Sharing Vary?

Abstract: We introduce a method for identifying social norms, based on the property that they reflect collective perceptions regarding the appropriateness of behaviors. We demonstrate that the norms we elicit, along with a simple model combining concern for norm-compliance with utility for money, predict changes in behavior across several variants of the dictator game. Our findings indicate that individuals care about monetary payoffs and the social appropriateness of any action taken. Further, we find that a social nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
277
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 702 publications
(403 citation statements)
references
References 57 publications
10
277
0
Order By: Relevance
“…This indicates that prosocial preferences do not depend on the difference between commissions and omissions as attributes of the action taken by a decision maker. It has been suggested that a utility maximization framework in the presence of social norms may benefit from including actions as an argument of the utility function (see, for example, [21,22]). Our results show that prosocial preferences are stable with respect to whether the choice is active or passive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that prosocial preferences do not depend on the difference between commissions and omissions as attributes of the action taken by a decision maker. It has been suggested that a utility maximization framework in the presence of social norms may benefit from including actions as an argument of the utility function (see, for example, [21,22]). Our results show that prosocial preferences are stable with respect to whether the choice is active or passive.…”
Section: Discussionmentioning
confidence: 99%
“…This means that actions themselves may affect social norms and moral concerns. In line with this notion, Levitt and List [21] and Krupka and Weber [22] argue that a utility maximization framework that aims at explaining choices under social norms can benefit from including actions as an argument in the utility function. Whether an outcome follows from an active choice or from the decision maker merely allowing for the outcome to be implemented is one such difference in how outcomes come about.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors argue [see, e.g., Camerer and Fehr (2004) or Krupka and Weber (2013)] that laboratory experiments can be used to gain at least an approximate quantification. Others, such as Levitt and List (2007), are more critical and point out that questions regarding a limited transferability of experimental situations to every-day-behavior have particular relevance for the case of adherence to social norms.…”
Section: Social Interactions and Social Normsmentioning
confidence: 99%
“…In recent years, experimental literature observed several different norms (e.g., [3,4]) to predict cooperative behavior. Although existing literature suggests that the establishment of norms can induce cooperation [5] (e.g., via reciprocity [6] or conditional cooperation [7]), norms are mainly added to economic research as post hoc interpretation [8]. Moreover, literature investigating how norms are formed and how one can use them to influence future behavior is scarce.…”
Section: Introductionmentioning
confidence: 99%